A Novel Multipath Routing Ring Protocol Adapted for WMSN - Bennani Mohamed Taj; Mhamed M. Ait Kbir (Institute of Advanced Engineering and Science, 2018)
In this paper an enhanced protocol of multipath routing ring that is suitable for transferring images by making many upgrades. First, instead of using propagation between the layers, we use certain parameters such distance and delay to pick the next node of the lower layer. Then, we used an heterogeneous network, including sensors (capture and send images) and connectors (serve as a bridge to the sink). Finally, we used the pyramid decomposition technique. To avoid congestion, we adjust the number of levels based on the state of the network. To verify our protocol, we used Castalia simulator to simulate the real transmission conditions. Then, we compared it with GPSR protocol and the original Multipath routing ring protocol. Our proposed protocol proves its efficiency by transferring more images with better quality (PSNR) and consuming less energy compared to other protocols.